(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article discusses the concept of communication in foreign language classes, comments given to it by world scientists, types of communication and public communication in social networks, the concept of speech, its manifestations and the impact of online communication on the speech process, as well as the positive effects of this process and negative aspects are analyzed.